Performance analysis in a probabilistic re-entrant for an environmental stress testing operation - OMAR, M; KUMAR, S (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper presents an extended approximation model based on mean value analysis (MVA) technique for a probabilistic re-entrant line. The objective is to develop a solution method to determine the total cycle time and mean throughput of the environmental stress testing (EST) operation for a given number of lots loaded into the system. Further work was done to determine the maximum number of lots that can be loaded into the system and the target cycle time. This paper also looks at alternative ways to assign human resources within the operation in the event of large number of lots required. Using analytical and simulation methods, comparison results were made for a five-stage queuing system with re-entrant lines into the second stage under various probabilistic routing conditions. The method proposed can be used by operation managers to determine their lots' cycle times, maximum number of lots and the operator assignments. (C) 2007 Elsevier Ltd. All rights reserved.